Driving behavior and road traffic crashes among professional and nonprofessional drivers in South Egypt. Issue 4 (2nd October 2019) - Arafa, Ahmed; El-Setouhy, Maged; Hirshon, Jon Mark
Abstract: Egypt has one of the highest traffic crash rates in the world. This study aims to investigate the correlates with driving behaviors and road traffic crashes (RTCs) among professional and nonprofessional drivers in South Egypt. A total of 518 drivers (203 professional and 315 nonprofessional) were interviewed and their sociodemographic characteristics, driving habits, and RTC involvement during the preceding 2 years were documented. The Arabic version of the Driver Behavior Questionnaire (DBQ) was used to assess drivers' lapses, errors, and violations. The results showed that professional drivers had more lapses (OR 3.03, 95% CI 1.54–5.96), errors (OR 2.88, 95% CI 1.44–5.76), and violations (OR 2.04, 95% CI 1.05–3.97) compared to nonprofessional drivers and female drivers were more likely to lapse than males (OR 3.18, 95% CI 1.79–5.66). RTC involvement was associated with female sex (OR 3.27, 95% CI 1.56–6.86), age < 30 years (OR 2.31, 95% CI 1.20–4.44), illiteracy (OR 1.51, 95% CI 1.02–2.23), eating while driving (OR 2.41, 95% CI 1.43–4.06), and not using seatbelt (OR 1.89, 95% CI 1.06–3.37). Driving lapses, errors, and violations did not significantly increase the risk of RTCs.